2023
DOI: 10.1371/journal.pbio.3002091
|View full text |Cite
|
Sign up to set email alerts
|

Streptothricin F is a bactericidal antibiotic effective against highly drug-resistant gram-negative bacteria that interacts with the 30S subunit of the 70S ribosome

Abstract: The streptothricin natural product mixture (also known as nourseothricin) was discovered in the early 1940s, generating intense initial interest because of excellent gram-negative activity. Here, we establish the activity spectrum of nourseothricin and its main components, streptothricin F (S-F, 1 lysine) and streptothricin D (S-D, 3 lysines), purified to homogeneity, against highly drug-resistant, carbapenem-resistant Enterobacterales (CRE) and Acinetobacter baumannii. For CRE, the MIC50 and MIC90 for S-F and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…Many non-ribosomal peptides have antimicrobial activity, and many serve as last-resort antimicrobial agents ( Liu et al, 2019 ). Notably, at least five different NRPSs ( Table 2 ) encode VITGV156, one of which is a well-known antibacterial agent, Streptothricin ( Morgan et al, 2023 ). The products of other NRPSs remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Many non-ribosomal peptides have antimicrobial activity, and many serve as last-resort antimicrobial agents ( Liu et al, 2019 ). Notably, at least five different NRPSs ( Table 2 ) encode VITGV156, one of which is a well-known antibacterial agent, Streptothricin ( Morgan et al, 2023 ). The products of other NRPSs remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Among the most intriguing on the list of 37 genes was RQC1, a component of the RQC pathway that resolves stalled ribosomes 36,37,76 . This was interesting because aneuploid strains are sensitive to translational inhibitor nourseothricin (NTC) that binds the ribosome to disrupt translation 13,22,[77][78][79] . Given that translation defects increase with cellular age [44][45][46] , these results raised the possibility that chromosome duplication induces defects in the RQC pathway.…”
Section: A Genetic Screen For Lifespan Extension Implicates the Rqc P...mentioning
confidence: 99%
“…Its therapeutic use was abandoned due to its induced reversible kidney toxicity; however, new cytotoxic studies have shown that streptothricin F exhibits at least 10-fold lower toxicity than streptothricin D and nourseothricin, both in vitro and in vivo. Moreover, streptothricin F has an alternative and unique mechanism of action, interacting with the 30S subunit of the 70S ribosome [53].…”
Section: Inhibition Of Protein Synthesismentioning
confidence: 99%